Outsourcing, unemployment and welfare policy - Christian Keuschnigg; Evelyn Ribi (Center for Economic Studies and ifo Institute (CESifo), 2008)
The paper investigates the consequences of outsourcing of labor intensive activities to low-wage economies. This trend challenges the two basic functions of the welfare state, redistribution and social insurance when private unemployment insurance markets are missing. The main results are: (i) outsourcing raises unemployment and labor income risk of unskilled workers; (ii) it increases inequality among high- and low-income groups; and (iii) the gains from outsourcing can be made Pareto improving by using a redistributive linear income tax if redistribution is initially not too large. We finally derive the welfare optimal redistribution and unemployment insurance policies.
Keywords: F23; H21; J64; J65; L23; 330; Outsourcing; unemployment; social insurance; redistribution; Outsourcing; Globalisierung; Arbeitslosigkeit; Ungelernte Arbeitskräfte; Soziale Sicherung; Verteilungswirkung; Sozialstaat; Offene Volkswirtschaft; Theorie